Interculturalism through a cognitive filter: Gilles Tremblay recomposes gamelan in Oralléluiants [1975] - Goldman, Jonathan (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2018)
In an article on the impact of gamelan music on Claude Debussy's musical language, Nicholas Cook shows Debussy's musical interpretations that navigate between viewpoints that claim that the gamelan presents "confirmation" of the principles that have been acquired by French composers and others who judge inspired techniques from the gamelan to imitate foreign musical culture. This article applies Cook's thought to the Javanese gamelan inspiration case in Oralléluiants (1975) by Gilles Tremblay (1932-2017), by trying to go beyond the opposition between pastiche orientalist style and deeper style assimilation by giving credit to the composer Québécois. This paper proposes the idea of "cognitive filters" as a way to understand how gamelan affects Tremblay without the same effect on other composers who are exposed to the same musical culture. The phrase "cognitive filter" shows every musical schematic that listeners have not mastered in terms of their training, ability, acculturation and psychological specificity, and that represents an order perceptual data to enable in the capture of previously unknown music.